A sleep analysis of elite female soccer players during a competition week - Thomas, C.; Jones, H.; Whitworth-Turner, C.; Louis, J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: (1) To compare the sleep of female players from a professional soccer team to nonathlete controls across an in-season week and (2) to compare the sleep of core and fringe players from the same team on the night after a match to training nights.